PERANAN APARAT KEPOLISIAN DALAM MENANGGULANGI PENYALAHGUNAAN NAPZA (NARKOTIKA, PSIKOTROPIKA DAN ZAT ADIKTIF) DI KALANGAN REMAJA - Asep Deni Normansyah (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2018)
Adolescence is a national bud that plays a role in the success of development because they are the successor of the older generation who inherited the ideals of the struggle and development of the country, though because of mental and adolescent behavior should not be damaged and involved in drug abuse. So that with such conditions can make everyone uneasy. The purpose of this research is to know the actions of Police Officers in providing mental guidance to Banjaran teenagers in order not to get involved in drugs. This research was conducted by using descriptive method, to obtain the data used in conducting observation, interview, questionnaire and literature study. The population studied were teenagers in the Village Margahurip is 685 people, who made the sample of 137 people. Based on the results of data obtained using Chi-quadrat formula shows that the role of police officers in overcoming drug abuse (Narcotics, Psychotropic and Addictive Substance) among adolescents in the Village Margahurip Banjaran, Bandung regency has been successfully implemented with a change in adolescent self and the existence good response from the Police Officers in the handling of the case of drugs as well as from the teenagers themselves. While the suggestion is to other authors should do researches that can change one's stance on the desire for success so it becomes a necessity. Because if someone considers desire to be a necessity then someone always wants to change.